Frequency of middle mesial canal in mandibular first molars and its association with various anatomic variables. (20th December 2021) - Bhatti, Usman Anwer; Muhammad, Muhammad; Javed, Muhammad Qasim; Sajid, Muhammad
Abstract: This study aimed to determine the frequency of the middle mesial canal in the mandibular first molars and its association with various anatomical features. Two experienced endodontists evaluated 149 CBCT images, containing n = 298 mandibular first molars and n = 298 mandibular second molars. Binary logistic regression was used to explore the relationship between the presence of middle mesial canal and other independent variables. The middle mesial canal was found in 7.7% ( n = 23) of mandibular first molars and 11.4% of which exhibited adjacent C‐shaped mandibular second molars. The presence of an adjacent C‐shaped mandibular second molar was associated with a 3 times increased likelihood of finding a middle mesial canal ( P = 0.048, OR: 3.108) in mandibular first molars. The middle mesial canal is an uncommon finding with a rare occurrence of bilateral presence in mandibular molars; however, an adjacent C‐molar is an important predictor of middle mesial canal presence.